DETERMINASI LOYALITAS KARYAWAN (SWASTA) GENERASI MILENIAL DI KOTA SURAKARTA - Iswati, Rachmadhita Nur; Kade R, Ida Ayu (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
Employee Loyalty is an attitude of obedience or employee loyalty to a company. The purpose of this study was to determine the relationship between work-life balance determination, organizational climate, career development and job characteristics on employee loyalty. The population in this study were employees (private) of the millennial generation of Surakata City using multiple linear analysis, sampling technique with simple random sampling and the Lemeshow formula as the sample calculation and processed using SPSS 28.0 for windows. The research method uses quantitative methods by distributing questionnaires to 100 respondents. The results showed that worklife balance, organizational climate, career development and job characteristics had a significant simultaneous effect on employee loyalty, but the worklife balance factor partially had no significant effect on employee loyalty.